2017
DOI: 10.1001/jamapediatrics.2017.2397
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Preexposure Prophylaxis for Adolescent Men

Abstract: Improving firearm storage inAlaska native villages: a randomized trial of household gun cabinets. Am J Public Health. 2012; 102(suppl 2):S291-S297.12. Garbutt JM, Bobenhouse N, Dodd S, Sterkel R, Strunk RC. What are parents willing to discuss with their pediatrician about firearm safety? a parental survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…4 Additionally, less than 7% of PrEP prescriptions have gone to men under 25. 5 To better understand the slow rate of PrEP uptake, several recent studies assessed whether participants were aware of PrEP and whether they had ever used PrEP in their lifetime. 68 Data also indicate differences in PrEP awareness and usage patterns across various groups, including lower rates of each among Black and transgender individuals.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, less than 7% of PrEP prescriptions have gone to men under 25. 5 To better understand the slow rate of PrEP uptake, several recent studies assessed whether participants were aware of PrEP and whether they had ever used PrEP in their lifetime. 68 Data also indicate differences in PrEP awareness and usage patterns across various groups, including lower rates of each among Black and transgender individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Older participants were 1.97 times more likely to have protective levels than younger participants. At week 24, older participants (ages 19-22) were 2.4 times more likely than younger participants (ages [15][16][17][18] to have protective levels. Perception of risk also approached significance at 12 and 24 weeks with participants who reported missing their medication because they were not having risky sex 91.6 and 92 percent (OR, 95% CI, p-value 0.022; OR, 95% CI, p-value 0.016, respectively) being less likely than participants who did not report this reason to have protective TFV-DP levels.…”
Section: Resultsmentioning
confidence: 99%
“…Some have suggested that younger adolescents will require not only additional visits than what is currently recommended by national guidelines, but also team members that can address these needs and help youth incorporate PrEP into their daily lives. 17 The ability to develop abstract thinking, plan for one's future, and integrate a positive adult identity, while simultaneously managing potential disapproval of same-sex behavior, and daily medications for HIV prevention, is likely to require an interdisciplinary developmentally-centered approach needed to support optimal adherence.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 The 2018 Food and Drug Administration approval for use of pre-exposure prophylaxis among adolescents at risk for HIV acquisition 92 will hopefully spur additional research on implementation for SGM youth, which has specific challenges related to parental consent, confidentiality, and health privacy. [93][94][95] More broadly, there is a need for a shift from such models of health disparity, where health imbalances and antecedent risk and protective factors are identified, to health equity and the identification of interventions to successfully overcome these disparities. The former studies require population-based epidemiologic and developmentally based cross-sectional or longitudinal designs, whereas the latter require rigorous intervention trials.…”
Section: Methodsmentioning
confidence: 99%